DEVELOPMENT OF RENEWABLE ENERGY AS A FACTOR FOR ENSURING SUSTAINABLE DEVELOPMENT OF COMMUNITIES IN THE CONTEXT OF THE EUROPEAN GREEN COURSE - Башинська, Юлія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article analyzes the possibilities of developing renewable energy as a factor in ensuring sustainable development of communities in the context of the European Green Deal using the example of communities in the western region of Ukraine. Since renewable energy is defined by the European integration course and international obligations of Ukraine as a key factor in the post-war economic recovery of communities, it is advisable to analyze the main determinants of its development in communities using the example of communities in the western macro-region of Ukraine, where, depending on the security situation, the construction of industrial-scale renewable energy facilities is possible. The article identifies factors for the recovery and transformation of the economy of communities on the basis of sustainable development through the “green” energy transition. The Western region of Ukraine is not in an active combat zone, but given that its energy infrastructure has also been significantly damaged by Russian missile and drone bombing, a strategic focus on rebuilding the region’s energy infrastructure based on “green” energy is extremely relevant and will contribute to the long-term stability and sustainable development of the region. The article outlines modern approaches necessary to realize the synergy between economic recovery and the implementation of renewable energy in the context of the European Green Deal. The key factors influencing the development of renewable energy in the Western region of Ukraine in wartime conditions are analyzed. It is determined that the combination of environmental requirements with economic strategies, as well as an advantageous border location, will contribute to attracting foreign investment in creating a reliable and diversified energy sector in the region. As the country simultaneously struggles to rebuild its infrastructure and stabilize its economy, renewable energy is becoming a key element in attracting investment and sustainable community development. The drive for energy independence aligns with the country’s national goals for social and economic recovery, laying the foundation for a transformational path to sustainable development. Based on the analysis, recommendations are made to accelerate the development of renewable energy in Ukraine in the context of the European Green Deal, using the example of communities in the western region of Ukraine.